2015
DOI: 10.1161/circgenetics.113.000690
|View full text |Cite
|
Sign up to set email alerts
|

ZBTB17 ( MIZ1 ) Is Important for the Cardiac Stress Response and a Novel Candidate Gene for Cardiomyopathy and Heart Failure

Abstract: M utations in >50 genes, mostly encoding sarcomeric and Z disc proteins, cause hypertrophic cardiomyopathy (HCM) and dilated cardiomyopathy (DCM) that lead to heart failure.1 Genetic variation in a Z disc gene can cause various forms of cardiomyopathies such as HCM or DCM perhaps because of pleiotropic effects on survival and hypertrophic pathways. 2 The muscle LIM protein (cysteine and glycinerich protein 3 [CSRP3]) is a Z disc protein involved in cardiac mechanosensation that is important for myocyte-specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 54 publications
(46 reference statements)
1
11
0
2
Order By: Relevance
“…The area of collagen I was calculated as percent of positive labelling per tissue area. Quantification of apoptotic cells was performed as described 48 . Sarcomere length was measured by intensity profiles of α-actinin in XYZ axes using the three-dimensional extended “Section” mode of the Imaris 7.7 program.…”
Section: Methodsmentioning
confidence: 99%
“…The area of collagen I was calculated as percent of positive labelling per tissue area. Quantification of apoptotic cells was performed as described 48 . Sarcomere length was measured by intensity profiles of α-actinin in XYZ axes using the three-dimensional extended “Section” mode of the Imaris 7.7 program.…”
Section: Methodsmentioning
confidence: 99%
“…31,[38][39][40][41][42][43][44][45] Similarly, recent in vitro and in vivo analyses of ZBTB17 have identified an anti-apoptotic gene product critical for the adaptation of cardiomyocytes to biomechanical stress. 46 Alongside our human genetic observations at these two loci, the data advocate for the pursuit and prioritization of other DCM signals with similar prognostic and therapeutic implications to advance current understanding of HF genetics.…”
Section: Discussionmentioning
confidence: 90%
“…ZBTB17 is also encoded on chromosome 1, at the 1p36 locus. A study of cardiac myocytes and a mouse model of ZBTB17 deletion demonstrated that ZBTB17 is involved in cardiac myocyte hypertrophy and is essential for cell survival [ 53 ]. The authors also showed that ZBTB17 encodes a transcription factor (zinc-finger and BTB domain-containing protein 17) that binds the gene CSRP3 , a Z-disc protein, mutations of which are found in both HCM and DCM.…”
Section: Genetic Factors Affecting Dilated Cardiomyopathymentioning
confidence: 99%
“…The second SNP was located within an intron of transcription factor gene ZBTB17 (rs10927875, 3.6 × 10 –7 ) [ 32 ]. ZBTB17 has since been postulated to be involved in cardiomyopathy in a mouse model, as discussed above [ 53 ]. However, the genomic region of this second locus contains many other genes, including heat-shock protein gene HSPB7 , which has been linked to heart failure syndromes multiple times.…”
Section: Genetic Factors Affecting Dilated Cardiomyopathymentioning
confidence: 99%